PROYECTO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA CAJA DE AHORRO EN LA PARROQUIA COLAISACA CANTÓN CALVAS, PROVINCIA DE LOJA - Gonza Valladares, Lucila Margarita (2016)
The present investigation has been developed as degree thesis prior to obtaining the degree of engineer in banking and finance, which has as purpose to contribute with a proposal to solve the current problems of savings and credit, creating opportunities to generate revenue that will help to improve the standard of living to the most fragile sectors. The project, discusses the feasibility study for the creation of a savings in the parish Colaisaca of the Canton of Calvas, which consists of four specific objectives such as: market research, technical, administrative and financialThe project, discusses the feasibility study for the creation of a savings in the parish Colaisaca of the Canton of Calvas, which consists of four specific objectives such as: market research, technical, administrative and financial. The creation of the savings, formulated a model with vision and social mission, that promotes the general welfare, whose purpose is to encourage savings and grant credits, with a simple but effective organizational structure with clear and specific functions that allow to offer adequate and timely products and services existing in the box. With regard to the first objective specific market research, was conducted to determine the degree of acceptability of the box of credit unions in the sector, and financial services offering. This study failed to set the demand 6 potential it reflecting projected once an a total of 514 people in the first year, with 490 people Real demand, the demand effective 359 people; also is accomplished to determine the supply and the demand for the creation of the savings it showing an unsatisfied demand of 211 members, so it is determined that it is a suitable place for the development of the project. According to the second objective was the technical study it sewn on the location, size and other elements that is required for the installation and operation of the saving box, and set the location and size of the Organization, stating that box will work on the premises of parish GAD. Likewise of determines the engineering of the project which has an installed capacity of 85%. As regards the administrative and Legal study, it contains a number of requirements for the functioning of the savings as well as organizational structures, functions and regulations manual. Finally the economic study refers to the investment required to implement the project $4965,69 $ detailed between fixed, current assets and working capital are indispensable for the implementation of the said project. A very essential part is the financial evaluation where calculations are shown in the VAN (net present value) is $2289,07, the 33,21% IRR (internal rate of return); Cost benefit corresponding to $1.11, indicating that for every dollar invested is perceived a utility of 0.11 cents, the Capital recovery period is 2 years, 5 months and 5 days and sensitivity analysis, with increases in the 7 costs of 13.78% and 7,11% revenue decrease, give as a result 0.99% and 0.98% respectively, which demonstrates the feasibility of the project, it must be made CALRE that this project is susceptible before any unforeseen arising. Using the methodology, there are conclusions, recommendations, bibliography and annexes which are necessary to present.